Biologically active substances in the ration of pigs on feed - A. V. Yarmots (Новые технологии)
One of the methods for increasing the productive output of nutrients from feed rations is the use of biologically active substances. We have tested some of them, which are the cheapest and the most available. The aim of the study was to evaluate growth, feed costs for pigs that received various sources of biologically active substances.